Phenylketonuria and glycogen storage disease type III in sibs of one family - Yılmazer, Tuncay; van Gennip, Albert H.; Abeling, Nico G.G.M.; Özalp, İmran and Coşkun, Turgay and Bakker, Henk D. (The Turkish Journal of Pediatrics, 2002)
Hyperphenylalaninemia result from a block in the conversion of phenylalanine into tyrosine due to a defect in either the enzyme phenylalanine hydroxylase (98% of subjects) or in the metabolism of the cofactor tetrahydrobiopterin. Phenylalanine hydroxylase deficiency is the most common form of inherited hyperphenylalaninemia disorders, with a prevalence between 1/4,000-1/40,000. Glycogen storage disease (GSD) type III is caused by debranching enzyme deficiency of glycogen degradation. The clinical features vary in relation to the localization of the enzyme defect. Two clinical entities exist: a combined hepatic myogenic form (GSD IIIa) and a purely hepatic form (GSD IIIb). The inheritance is autosomal recessive. We describe a Turkish family in which two girls were found to have phenylketonuria, while in two other sisters glycogen storage disease type III was diagnosed. The parents of these children are cousins and they have had 12 children.